Is It Personal? The Effect of Personal vs. Occupational Trauma on PTSD Symptom Severity in Emergency Responders - Wild, Jennifer; Chang, Tingyee E. (Frontiers in Psychiatry, 2022)
Emergency responders are exposed to potentially traumatic events in their line of work and as such, are at increased risk of developing post-traumatic stress disorder (PTSD). Little is known about the characteristics of trauma associated with PTSD symptoms in this population. This study analysed the self-reported worst traumatic event on the PTSD checklist for DSM-5 for a sample of N=610 emergency responders, working as police officers, paramedics, firefighters or search and rescue personnel. Sufficient information was available to code 98% (N=603) participants’ trauma; 84% (N=509) met DSM-V criterion A trauma. Of the participants reporting criterion A trauma, 56.9% (N=290) participants reported being most affected by a traumatic event that occurred in their personal lives, 41.5% (N=211) participants reported being most affected by a work-related traumatic event and 1.6% (N=8) reported criterion A events that were work-related and had occurred prior to their role as an emergency responder (e.g., combat). Paramedics were significantly more likely to report occupational trauma as their worst event whereas police officers, firefighters, and search and rescue workers reported personal trauma as their worst event. Personal trauma was associated with significantly greater PTSD symptom severity than occupational trauma. Emergency responders identifying as women were significantly more likely to report personal than work-related trauma as their index event and men were more likely to report work-related than personal trauma as being linked to their PTSD symptoms. The results underscore the need to consider the broader context of trauma in the emergence of PTSD symptoms in emergency workers.